The Behavior of Reinforced Concrete Beams Added Cold-Formed-Steel as Shear Reinforcement - Puluhulawa, Indriyani; Alamsyah; Husna, Rosyidatul (Journal of Structural Monitoring and Built Environment, 2022)
This paper presents an experimental study of concrete beams with cold formed steel added as shear reinforcement. Previous researchers have shown that cold formed steel has a yield stress of generally 350 MPa to 550 MPa, but its use is still mostly focused on anticipating beam bending. The purpose of this study was to determine the behavior of concrete beams with cold formed steel added as stirrup to increase the shear capacity of the beam. Two beams have been made with a size of 150x250x860 mm. one as a control beam, the other as a beam with CFS added as reinforcement for stirrups with a width of 20 mm, a thickness of 0.75 mm with a spacing of 120 mm. The results have shown that the increase in the shear capacity of the beam with the addition of CFS is 12.7% even though according to Response2000 analysis it is 38.7%. The failure that occurs is a shear failure in accordance with the predetermined a/d ratio.